(untitled) (MAUSAM, 2016)
Dryland areas account for 48% of area under food crop and 52% under non-food crop cultivation and contribute about 42% of total food grain production in India. Drought is the predominant weather extreme influencing the socio-economic structure of not only dry land regions but also the entire country. Various drought monitoring techniques and mechanisms aim at mitigating the drought impacts at different spatial scales. They are discussed briefly here with strategies to cope up this weather anomaly at different time scales. Dry land districts that are prone to frequent hail episodes are identified and measures to minimize damage to agriculture are also discussed.